2016
DOI: 10.1111/jgh.13219
|View full text |Cite
|
Sign up to set email alerts
|

Controlled attenuation parameter for the diagnosis of steatosis in non‐alcoholic fatty liver disease

Abstract: Background and Aim: Controlled attenuation parameter (CAP) evaluated with transient elastography (FibroScan) is a recent method for non-invasive assessment of steatosis. Its usefulness in non-alcoholic fatty liver disease (NAFLD) is unknown. We prospectively investigated the performance of CAP for the diagnosis of steatosis in NAFLD, factors associated with discordances between CAP and steatosis grades, and relationships between CAP and clinical or biological parameters. Methods: All CAP examinations performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
132
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 21 publications
7
132
2
1
Order By: Relevance
“…Significantly higher CAP values were seen in patients with S2/S3 steatosis compared to S1 (333 versus 285 dB/m; p < 0.001), and the AUROC of CAP to detect ≥ S2 and S3 was 0.8 and 0.66, respectively [12]. The optimal CAP cut-off for ≥ S2 disease was 310 dB/m [12], which provided a correct assessment of S2/S3 in 86% of the cohort [12]. Discordance of at least one grade between CAP and histology was observed in 31% of the patients.…”
Section: Controlled Attenuation Parametermentioning
confidence: 94%
See 3 more Smart Citations
“…Significantly higher CAP values were seen in patients with S2/S3 steatosis compared to S1 (333 versus 285 dB/m; p < 0.001), and the AUROC of CAP to detect ≥ S2 and S3 was 0.8 and 0.66, respectively [12]. The optimal CAP cut-off for ≥ S2 disease was 310 dB/m [12], which provided a correct assessment of S2/S3 in 86% of the cohort [12]. Discordance of at least one grade between CAP and histology was observed in 31% of the patients.…”
Section: Controlled Attenuation Parametermentioning
confidence: 94%
“…Overall, CAP values for S0, S1, S2 and S3 were 264 ± 45, 298 ± 48, 331 ± 37 and 336 ± 31 dB/m, respectively [12]. Significantly higher CAP values were seen in patients with S2/S3 steatosis compared to S1 (333 versus 285 dB/m; p < 0.001), and the AUROC of CAP to detect ≥ S2 and S3 was 0.8 and 0.66, respectively [12]. The optimal CAP cut-off for ≥ S2 disease was 310 dB/m [12], which provided a correct assessment of S2/S3 in 86% of the cohort [12].…”
Section: Controlled Attenuation Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…A preliminary study in a mixed population of diffuse liver disease reported high correlation of CAP with histological steatosis grade (correlation coefficient 0.81) with excellent severity grading performance and high reproducibility [20]. In a NAFLD population, validation data are still incomplete, but CAP has thus far shown promise as a standardized quantitative US biomarker for steatosis [19, 21]. However, further validation is needed, including evaluation of newer probes optimized for obese patients.…”
Section: Conventional Imagingmentioning
confidence: 99%